PELARANGAN PENGGUNAAN GADGET BAGI PESERTA DIDIK MELALUI PENGAMBILAN KEPUTUSAN ETIS GURU DI SMK NEGERI 1 SIGUMPAR - Siagian, Samuelson Halomoan; Carisma Marbun, Rencan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2024)
This research aims to explore the implementation of the policy of prohibiting the use of gadgets at SMK Negeri 1 Sigumpar and its impact on the learning process and students' ethical views in the context of Christian education. The increasingly widespread use of gadgets among students has both positive and negative impacts, including dependence on technology and potential disruption in the learning process. Using qualitative methods, data was collected through interviews with teachers, students and parents, as well as observations of the implementation of these policies in schools. The results of the research show that the policy of banning gadgets at SMK Negeri 1 Sigumpar has had a positive impact, such as increasing student concentration, reducing distractions, and increasing social interaction in the classroom. From an ethical perspective, this policy provides important lessons about managing technology in an educational context, taking into account the balance between the use of technology and the need for healthy interpersonal relationships in the school environment. Therefore, although banning gadgets provides benefits in reducing disruption to learning, schools need to consider improving facilities and teaching methods that support education without ignoring technological developments. This policy should be supported by training for teachers and students as well as parental involvement in the process of monitoring the wise use of technology.